Obstructive sleep apnea and anatomical structures of the nasomaxillary complex in adolescents - Jeong-Hyun Kang; Hyun Jun Kim; Seung Il Song (PLoS ONE, 2022)
The aim of the present study was to reveal the associations between skeletal and soft tissue features of the nasomaxillary complex and development and severity of obstructive sleep apnea (OSA) in adolescents. A total of 100 adolescents (mean age, 14.9 ± 1.4 years; age range, 13–17 years) were enrolled. All participants underwent full-night polysomnography and had an assessment of size and position of the tongue, tonsillar size, body mass index (BMI), and circumference of the waist, neck, and hip. The skeletal features of the nasomaxillary complex, including the zygomatic arch width, nasal cavity width, nasal base width, intercanine width, intermolar width, maxillary dental arch length, palatal vault angle, palatal depth, and SNA were measured on the three-dimensional images constructed with computed tomography data. Participants with an apnea and hypopnea index (AHI) of lower than 5 (AHI ≤ 5) were classified as control and participants while those with an AHI of greater than 5 were classified as OSA group. Each variable with a significant outcome in the independent T-test and age and sex factors were integrated into the multivariate linear regression and the dependent variable was AHI. There were significant differences in the BMI and hip circumference between two groups. The width of nasal base, palatal vault angle and SNA also showed significant differences between groups. The results from multivariate linear regression demonstrated that the BMI, width of the nasal base, and SNA showed significant contributions to the severity of OSA in adolescents. The features of the nasomaxillary complex seemed to have significant influences on development and severity of OSA.